ANALISIS KEPUASAN KONSUMEN TERHADAP PELAYANAN KEFARMASIAN DI APOTEK PUSPA INDAH FARMA DENGAN MENGGUNAKAN METODE IMPORTANCE PERFORMANCE ANALYSIS (IPA) - Ardianto, Nanang; Sekti, Beta Herilla (Institut Teknologi, Sains, dan Kesehatan RS.DR. Soepraoen Kesdam V/BRW, 2024)
Pharmaceutical services are a benchmark for pharmaceutical technical personnel in services at pharmacies in order to improve quality of life, quality service and consumer satisfaction. The aim of this research to determine satisfaction with each item in pharmaceutical services at Puspa Indah Farma pharmacy. This research involved 100 consumers who purchased prescription drugs cash at Puspa Indah Farma Malang Pharmacy using Importance Performance Analysis (IPA) method. The research design used was descriptive quantitative